(untitled) (Bangladesh Journal of Agricultural Research, 2016)
Seventeen genotypes of bitter gourd (Momordica charantia L.) were studied in a field experiment conducted at the experimental field of Sher-e-Bangla Agricultural University, Dhaka, during April 2009 to September 2010. The objectives of the study were to measure the variability among the genotypes for yield and yield contributing characters, estimate genetic parameters, association among the characters and their contribution to yield. There was a great deal of significant variation for all the characters among the genotypes. Considering genetic parameters high genotypic co-efficient of variation (GCV) was observed for branches per vine, yield per plant and number of fruit per plant whereas low genotypic co-efficient of variation (GCV) was observed for days to first male and female flowering. In all the cases, it was found that phenotypic co-efficient of variation was greater than genotypic co-efficient of variation. Highest genotypic and phenotypic co-efficient of variation was observed in branch per vine, fruit length, fruit weight and number of fruit plant which indicated a wide variability among the genotypes and offered better scope of selection. The results obtained showed that fruit length showed low direct and positive effect on yield per plant and indirect positive effect on yield per plant via fruit diameter and average fruit weight. Similar result was found for fruit diameter. Average fruit weight and number of fruits per plant showed high direct and positive effect on yield per plant. Path analysis revealed that average fruit weight, number of fruits per plant, days to male flowering and fruit length had positive direct effect on fruit yield. Considering group distance and the agronomic performance, the inter genotypic crosses between G2& G5; G2&G14; G14&G15; G2&G15; G10&G11; G10&G13; G11&G13; G5&G15; G5&G14 might be suitable choice for future hybridization programme. Bangladesh J. Agril. Res. 40(4): 607-618, December 2015